NUMERICAL-SIMULATION OF THE TEMPERATURE-DEPENDENCE OF THE SIDEGATING EFFECT IN GAAS-MESFETS - CHANG, SJ; LEE, CP (My University, 1994)
The temperature dependence of the sidegating effect in GaAs devices has been investigated by performing two-dimensional numerical simulations on realistic structures. The less sidegating and the higher sidegating threshold at higher temperatures are found to be caused by the temperature-dependent trapping properties of the deep traps and the difference in increase rate with temperature of the currents in various current paths. These results provide further support lo the sidegating picture in which Schottky contacts on the semi-insulating substrate play an important role.